2006
DOI: 10.4049/jimmunol.176.9.5471
|View full text |Cite
|
Sign up to set email alerts
|

TAT-BH4 and TAT-Bcl-xL Peptides Protect against Sepsis-Induced Lymphocyte Apoptosis In Vivo

Abstract: Apoptosis is a key pathogenic mechanism in sepsis that induces extensive death of lymphocytes and dendritic cells, thereby contributing to the immunosuppression that characterizes the septic disorder. Numerous animal studies indicate that prevention of apoptosis in sepsis improves survival and may represent a potential therapy for this highly lethal disorder. Recently, novel cell-penetrating peptide constructs such as HIV-1 TAT basic domain and related peptides have been developed to deliver bioactive cargoes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
74
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 35 publications
9
74
1
Order By: Relevance
“…In accordance with our results, Iwata et al reported that mice which were transgenic for Bcl-2 in their myeloid-derived cells had decreased sepsis-induced apoptosis in their intestinal epithelial cells [8]. The mechanism of this cross-protection is unknown but has been reported by other groups [5][6][7][8][9][10]. Iwata et al speculated, however, that the protective action of Bcl-2 over expressing cells was via a "trans" effect, i.e., Bcl-2 over expressing cells released an unknown cytoprotective factor which prevented death in non-Bcl-2 over expressing cells of distinct and distant lineages.…”
Section: Introductionsupporting
confidence: 91%
“…In accordance with our results, Iwata et al reported that mice which were transgenic for Bcl-2 in their myeloid-derived cells had decreased sepsis-induced apoptosis in their intestinal epithelial cells [8]. The mechanism of this cross-protection is unknown but has been reported by other groups [5][6][7][8][9][10]. Iwata et al speculated, however, that the protective action of Bcl-2 over expressing cells was via a "trans" effect, i.e., Bcl-2 over expressing cells released an unknown cytoprotective factor which prevented death in non-Bcl-2 over expressing cells of distinct and distant lineages.…”
Section: Introductionsupporting
confidence: 91%
“…Many therapeutic cargo molecules have been successfully delivered into cells via CPPs including proteins, peptides, si-RNA, DNA, and others (van den Berg and Dowdy, 2011;Zorko and Langel, 2005). TAT-BH4 and TAT-Bcl-XL inhibited sepsis-induced apoptosis of lymphocytes in vivo (Hotchkiss et al, 2006) and TAT-Cre was used to generate conditional knock-out mice (Wadia et al, 2004). Polyarginine (11R)-conjugated VIVIT peptide, which is a specific NFAT inhibitory peptide, was able to inhibit graft rejection of allogeneic islet transplantation in mice (Noguchi et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The cell membrane permeable TAT-Bcl-X L peptide construct as well as a TAT-conjugated peptide of the anti-apoptotic BH4 domain of Bcl-X L (TAT-BH4) decreased sepsis-induced splenocyte T-and B-cell apoptosis to near sham levels in experimental murine sepsis. TAT-Bcl-X L prevented Escherichia coli-induced human lymphocyte apoptosis ex vivo and markedly decreased lymphocyte apoptosis in an in vivo mouse model of sepsis [58].…”
Section: Inhibiting Apoptosis Improves Septic Survival -Therapeutic Omentioning
confidence: 94%